2023
DOI: 10.55869/kppu.v3i2.130
|View full text |Cite
|
Sign up to set email alerts
|

Urgensi Pemberlakuan Indirect Evidence pada Penanganan Perkara Kartel di Indonesia

Girli Ron Mahayunan,
Ronald Eberhard Tundang,
Joanna Christie Tan

Abstract: Kelangkaan dan harga minyak goreng yang tinggi menjadi masalah pelik sejak akhir tahun 2021 dan berlanjut sampai dengan pertengahan 2022. Harga minyak goreng melambung tinggi dengan peningkatan sebesar empat puluh persen dari tahun sebelumnya pada bulan Januari 2022. Pada saat itu, harga kelapa sawit mentah juga mengalami kenaikan yang mendorong perusahaan kelapa sawit untuk mengekspor ketimbang memenuhi kebutuhan dalam negeri. Hasil kajian yang dilakukan penulis menyatakan bahwa industri rantai pasokan minyak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this way, one piece of evidence is fulfilled, namely evidence of indication. This evidence needs to be corroborated by other evidence, for example, expert testimony (Mahayunan et al, 2023). The presentation regarding the legal considerations for the cooking oil cartel case by KPPU above, when viewed from the perspective of justice and legal certainty, it can be concluded that KPPU has acted fairly towards the general public who have been harmed by the price of cooking oil which remains expensive even though world CPO prices have fallen by giving a guilty verdict against the reported party and imposed administrative sanctions that should have been supported by the decisions of the District Court and the Supreme Court because KPPU is more detailed in placing or analyzing cartel cases where proving the articles must use the rule of reason approach, which means that for cartel cases themselves it is difficult to prove with direct evidence/written evidence.…”
Section: )mentioning
confidence: 90%
See 1 more Smart Citation
“…In this way, one piece of evidence is fulfilled, namely evidence of indication. This evidence needs to be corroborated by other evidence, for example, expert testimony (Mahayunan et al, 2023). The presentation regarding the legal considerations for the cooking oil cartel case by KPPU above, when viewed from the perspective of justice and legal certainty, it can be concluded that KPPU has acted fairly towards the general public who have been harmed by the price of cooking oil which remains expensive even though world CPO prices have fallen by giving a guilty verdict against the reported party and imposed administrative sanctions that should have been supported by the decisions of the District Court and the Supreme Court because KPPU is more detailed in placing or analyzing cartel cases where proving the articles must use the rule of reason approach, which means that for cartel cases themselves it is difficult to prove with direct evidence/written evidence.…”
Section: )mentioning
confidence: 90%
“…`In this cooking oil cartel case, the Supreme Court as the judex juris only examines the application of the law by KPPU to case No. 24/KPPUI/2009 concerning Cooking Oil Cartel (Mahayunan et al, 2023). The Indonesian Competition Supervisory Commission (KPPU) uses indirect evidence to prove cartel behavior, particularly in cases without written agreements.…”
Section: Challenges and Limitations In Indirect Evidence Collectionmentioning
confidence: 99%